Krabbe Disease Associated With Mitochondrial Dysfunction in a Chinese Family - Wu, Liwen; Liao, Xiangfu; Yang, Sai; Gan, Siyi (Frontiers in Neurology, 2021)
Background: Krabbe disease is caused by biallelic mutations of GALC gene. NDUFAF1 gene mutations are related to mitochondrial encephalopathy. To date, there is no report about the co-pathogenesis of these two gene mutations. There were three children in a family who presented with global developmental retardation, MRI showed lesions in the white matter and dentate nucleus of cerebellum. Methods: Clinical data of the proband and her family members were gathered in a retrospective manner. Karyotype, FISH, whole exome sequencing was performed using genomic DNAs extracted from the peripheral blood samples. The enzyme activities of GALC and mitochondrial enzyme activities were determined to verify the gene functions. Results: This study reported a pedigree of leukoencephalopathy in which 3 of the 4 children showed phenotypes of developmental delay, hearing/visual impairment, and peripheral neuropathy. Mutations of NDUFAF1(c.278A＞G; p. His93Arg, c.247G＞A; p. Asp83Asn) and GALC (c.599C>A; p.Ser200*) were identified in all the three cases. The proband’s parents carried these mutations as heterozygous states. The clinical features, MRI changes, enzyme activity of GALC and mitochondrial function analysis demonstrated that this pedigree was caused by GALC and NDUFAF1 gene mutations working together. Conclusion: We firstly report a pedigree of Krabbe disease with biallelic mitochondrial gene NDUFAF1 mutations. For multiple gene mutations found in genetic testing, clinical phenotypes, gene functions, and family histories should be comprehensively analyzed. Gene panel examination may miss pathogenic mutations, and prenatal diagnosis of patients with polygenic inheritance needs careful consideration.